Invertebrate diversity from corticolous moss in the Iztaccíhuatl Volcano region, Mexico State - CUTZ-P., LEOPOLDO Q.; GARCÍA-G., ARTURO; CASTAÑO-M., GABRIELA; PALACIOS-V, JOSÉ G. (Revista Colombiana de Entomología, 2010)
The diversity of invertebrates in corticolous moss was compared along an altitudinal gradient on the NW slope of the Iztaccíhuatl Volcano, in the central part of Mexico. Sixteen taxa of invertebrates from corticolous moss were recorded, among which the Mesostigmata, Prostigmata, Astigmata and Cryptostigmata were the most abundant, making up 81%. The Mesostigmata showed their maximum abundance (45%) at 3.020 m elevation, Prostigmata at 2.830 m (44%), Astigmata at 2.750 m (12%) and Cryptostigmata (75%) at 3,250 m. There was spatial variation in the density of invertebrates; the highest density was found at 3.250 m and the lowest at 2.750 m. The highest diversity was recorded between 2.750 and 2.930 m. The highest similarity was observed between 2.750 and 2.930 m. For the Opilionida, Cryptostigmata and Psocoptera there was a positive correlation between altitude and density while the density of Oligochaeta, Araneae and Hemiptera was negatively correlated with altitude.